2015
DOI: 10.1016/j.joa.2014.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased defibrillator therapies during influenza season in patients without influenza vaccines

Abstract: A trend toward more ICD therapies during influenza season was observed in patients who did not receive the influenza vaccine compared to those who did. The association was stronger in patients who received appropriate ICD shocks and in patients with left ventricular systolic dysfunction. Further work to confirm these findings is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…The electronic database search yielded 414 references. After removal of duplicates, screening of title and abstract and evaluation for full-text eligibility, eight studies remained for inclusion in the qualitative synthesis,9 22–28 and seven studies in the meta-analysis9 22 23 25–28 (figure 1) (online supplementary table 1). The remaining studies 24 were not included in the meta-analysis because they only reported surrogate outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic database search yielded 414 references. After removal of duplicates, screening of title and abstract and evaluation for full-text eligibility, eight studies remained for inclusion in the qualitative synthesis,9 22–28 and seven studies in the meta-analysis9 22 23 25–28 (figure 1) (online supplementary table 1). The remaining studies 24 were not included in the meta-analysis because they only reported surrogate outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Two secondary outcomes were evaluated by two studies: CV mortality26 28 and all-cause hospitalisation 9 27. Ventricular arrhythmias were evaluated in a study by Modin et al and by surrogate outcomes in a study by Singh et al which reported all implantable cardioverter defibrillator (ICD) therapies and ventricular arrhythmias/appropriate ICD shocks 24. HF-related hospitalisations and recurrent HF-related hospitalisations (HF-related hospitalisations on more than one occasion during follow-up) were only evaluated in one study 26.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing risk of ventricular arrhythmia during wintertime had been reported before ( 43 ). Moreover, increasing implantable cardiac defibrillator therapies was also observed during influenza season ( 44 ). However, the risk of myocardial infarction could increase even in hot weather ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic search of online databases revealed 360 articles (PubMed = 77, EMBASE = 260, Cochrane Library = 23). After excluding duplicates and screening the titles/abstracts, 24 articles were subjected to a more detailed full-text assessment, after which seven articles with 3,169,977 patients were included in the analysis (12)(13)(14)(17)(18)(19)(20) (Figure 1). The excluded studies and the reasons for their exclusion are listed in Supplementary Table 2.…”
Section: Study Selectionmentioning
confidence: 99%